EFFECTS OF A MINI-TRAMPOLINE EXERCISE DURING 15 WEEKS FOR INCREASING THE VERTICAL JUMP PERFORMANCE - Almir Atiković,; Amra Nožinović-Mujanović,; Edin Mujanović,; Jasmin Mehinović,; Jasmin Bilalić, (Sport Scientific And Practical Aspects, 2025)
Mini-trampoline exercise is becoming a very popular form of training. The purpose of this study is to examine the effects of 15-week trampoline training on vertical jump parameters in boys who do not exercise regularly. Methodsː The subjects (13 years +/- 6 months) old boys were randomly allocated to one of two groups: trampoline training group (TG, N=23) and control group (CG, N=29) to examine effects of 15-week trampoline training (1 time per week). Optojump we measure the following variables: time of flight phase (s), height of jump (cm), specific energy (J/kg) and total energy (J). Sixteen variables were used to estimate the explosive power of lower extremity: DJ drop jump 20cm, DJ drop jump 40cm, SJ squat jump and CMJ countermovement jump. The t-test was used to compares the means of two groups. For this analysis, the significance level is 0.05. Resultsː As a result; whereas 15 weeks of trampoline exercise improved vertical jump preformance of subjects. Differences between the pre-test and post-test in TG are statistically significant (P<0.05). TG in regards to CG differs in the height of the jump DJ20cm for 1.161 cm, DJ40cm for 0.580 cm, SJ for 0.141 cm and CMJ for 0.313 cm in benifit of TG. ConclusionsːThe trampoline training used in our study may form an example for the sports educators for improving the explosive strength of the lower extremities in children. Using a mini trampoline offers a variety of health benefits for the body.